High skilled immigration in the international arena - Barry R. Chiswick (Institute for the Study of Labor (IZA), 2005)
This conceptual paper, prepared for a United Nations Expert Group Meeting on Migration and Development, is concerned with the international mobility of high-skilled workers, previously referred to as the brain drain. After discussing the historical background of high-skilled international migration, the paper examines the reasons for the recent growth in demand for high-skilled workers in the technologically advanced nations. If then examines the impact of high-skilled migration on the level and distribution of income in the destinations. The causes and consequences of high-skilled emigration from the perspective of the origins or sending countries are examined. Educational finance and taxing policies that encourage emigration, emigrant remittances, and the brain gain from returning emigrants are discussed. Alternative public policies are considered.
Keywords: F22; J61; J31; O15; 330; immigration; high skilled workers; economic development